Assessment of transversal key competences in engineering careers in one Argentinean university in regard to the changes of students’ population (2002-2013) (Revista Electrónica Calidad en la Educación Superior, 2018)
Engineering careers lead us to deal with a pedagogical challenge: to teach contents with sophisticated theoretical contents to be applied in an ever changing world. Developing key transversal competences has been one of the answers to that challenge. Nevertheless, from the class, we need to accomplish this objective on an unfriendly institutional environment characterized by a fragmented knowledge accreditation model and the utilization of summative and quantitative evaluation criteria, in the frame of changes on quantity and social and professional backgrounds of the students’ population. This paper is a reflexive effort to analyze the evaluation strategies developed in a university placed on Buenos Aires surroundings in order to develop and asset key transversal competences.